Allium elazigense (Amaryllidaceae), a new species from eastern Anatolia, Turkey - Sonay, Veysel; Gul, Emel; Bagci, Eyup (Finnish Zoological Botanical Publishing Board, 2024)
Allium elazigense Sonay, G & uuml;l & E. Bagci, a new species of sect. Codonoprasum, is described and illustrated from eastern Anatolia, Turkey. It resembles A. chloranthum, but differs from it by several morphological characters. Allium elazigense has a brownish outer tunic that forms a collar on the spiral-shaped spathe valves with a dark brown midrib, greenish-creamy perigon, oblong outer tepals and spathulate-oblong inner tepals, short anthers and a short ovary, a cylindrical-oblong, stipitate capsule, and narrowly semi-cylindrical cymbiform seeds. Based on IUCN criteria, its conservation status is assessed as Critically Endangered (CR).
Keywords: Seed Morphology; Phylogeny